Fatores associados à piora do grau de incapacidade física durante o tratamento de hanseníase no Brasil - Costa, Letícia Gomes (2014)
Leprosy is a relevant public health problem due to its magnitude, and high disabling potential. Objective: To analyze factors associated with worsening physical disability grade during treatment of newly diagnosed cases of leprosy in Brazil in 2009. Methods: Cross-sectional study about associated factors of worsening physical disability grade during the treatment of PB and MB cohort leprosy cases. Data were collected from the National Reportable Diseases Database (SINAN). It was applied descriptive analysis of the variables and chi–square test at 5% level to compare proportions of worsening and not worsening of the disability grade. To analyze the variables associated with the worsening disability grade, logistic regression was used to determine the odds ratio (OR), with a confidence interval of 95%. Results: Among the Brazilian regions, patients in the Southern region were those with the greatest odds of worsening the physical disability grade (OR = 2.19; CI: 1.85 - 2.58), following were the Southeast cases with odds of 1.53 (CI: 1.36 to 1.73 ), both compared to the North region patients. Multibacillary presented odds ratioadj of 3.09 (CI: 2.83 - 3.40) and male cases of 1.27 (CI: 1.17 - 1,37) to worse. Seniors and adults compared to children had odds of 2.67 and 1.95 of worsening (CI: 2.13-3.34; 1.58-2.40 respectively), and the reactional cases had odds of 2.35 to worse (CI: 2.15 - 2:56). Conclusion: The factors associated with worsening physical disability grade during the treatment are composed by the patients residents in the South and Southeast regions, male cases, multibacillary, those that presented reactional episodes, seniors and adults, irregular cases as well as those with low scholarity.